Pendeteksian Manipulasi Laporan Keuangan pada Perusahaan Konstruksi Menggunakan Model Beneish M-Score - Sefrilia Sandra Komala; Fadillah Aditya Rahman; M Diarama Kurnia Putra; Sulistiawati Sulistiawati; Yanuar Ramadhan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to detect potential financial statement fraud in the Indonesian construction sector using the Beneish M-Score model. This study aims to test how effective this model can function as an early warning tool in identifying accounting manipulation in public companies. This study uses a quantitative descriptive approach. Secondary data were obtained from audited annual financial statements of five large construction companies listed on the Indonesia Stock Exchange for the fiscal years 2023 and 2024. The Beneish M-Score model was applied using eight financial ratios (DSRI, GMI, AQI, SGI, DEPI, SGAI, TATA, and LVGI), and the results were interpreted based on the set threshold of -2.22. The analysis showed that four companies did not exhibit signs of manipulation, with M-Scores below -2.22. However, PT Waskita Karya showed a partial M-Score of -1.82, indicating a strong signal of potential financial statement fraud. This highlights the relevance of the model in identifying warning signs, particularly in companies with complex financial structures. This study is limited by the partial calculation of M-Score components due to data availability constraints (e.g., DEPI, SGAI, TATA, LVGI). Additionally, this study does not involve forensic audits to confirm actual fraud. Nevertheless, this study suggests that regulators, investors, and auditors should integrate the Beneish model as an initial filter in assessing fraud risk, particularly in project-based and capital-intensive industries such as construction.